Conservation implications for dingoes from the maternal and paternal genome: Multiple populations, dog introgression, and demography. Issue 22 (19th October 2017) - Cairns, Kylie M.; Brown, Sarah K.; Sacks, Benjamin N.; Ballard, J. William O.
Abstract: It is increasingly common for apex predators to face a multitude of complex conservation issues. In Australia, dingoes are the mainland apex predator and play an important role in ecological functioning. Currently, however, they are threatened by hybridization with modern domestic dogs in the wild. As a consequence, we explore how increasing our understanding of the evolutionary history of dingoes can inform management and conservation decisions. Previous research on whole mitochondrial genome and nuclear data from five geographical populations showed evidence of two distinct lineages of dingo. Here, we present data from a broader survey of dingoes around Australia using both mitochondrial and Y chromosome markers and investigate the timing of demographic expansions. Biogeographic data corroborate the presence of at least two geographically subdivided genetic populations, southeastern and northwestern. Demographic modeling suggests that dingoes have undergone population expansion in the last 5, 000 years. It is not clear whether this stems from expansion into vacant niches after the extinction of thylacines on the mainland or indicates the arrival date of dingoes. Male dispersal is much more common than female, evidenced by more diffuse Y haplogroup distributions. There is also evidence of likely historical male biased introgression from domestic dogs into dingoes, predominately within southeastern Australia. These findings have critical practical implications for the management and conservation of dingoes in Australia; particularly a focus must be placed upon the threatened southeastern dingo population. Abstract : Dingoes are the Australian terrestrial apex predator. There are key knowledge gaps concerning the origin, biogeography, and population genetics of dingoes. We present data from a broad survey of dingoes around Australia using both mitochondrial and Y chromosome DNA markers and investigate the timing of demographic expansions. Our data have important implications for the conservation and management of dingoes in Australia.